Development and Validation of Information Technology (IT) Based Instrument to Measure Teachers' IT Preparedness - Wong, Su Luan (2002)
The Malaysian Ministry of Education plans to turn approximately 10,000 primary and secondary schools into Smart Schools which emphasise the use of Information Technology (IT) by the year 2010. This means that all teachers must be fully prepared to teach in Smart Schools nation-wide. The pressure on teachers has, therefore, become urgent. For this reason, there is a growing educational interest in the assessment of teachers' IT preparedness. This study attempts to develop and validate a n instrument to measure teachers' IT preparedness. IT preparedness is measured in three domains: the teachers' actual IT skills, their knowledge about IT and their attitudes toward IT. Initially, three tables of content specification were constructed for each domain. These tables comprised two dimensions. Actual IT skills were measured in terms of content (word processing, electronic spreadsheet, electronic database, electronic presentation and the Internet) and task categories (basic operation, manipulation and design); knowledge about IT was measured in terms of content categories (system hardware, system software and the Internet) and Bloom's taxonomy (knowledge, comprehension and application); attitudes were measu red in terms of content categories (the Internet, specific software applications, software applications in general, computer and IT in general) and four sub-domains (usefulness, confidence, anxiety and a version).